Dekonstruksi Estetika dan Makna Musik Gamat di Sawahlunto, Sumatera Barat - Murniati Murniati (Institut Seni Indonesia Yogyakarta, 2015)
Keberagaman budaya masyarakat lokal terlihat dari kekayaan ekspresi seni budaya masyarakat,di antaranya terdapat pada musik gamat. Tulisan ini melihat dekonstruksi estetika dan makna darifenomena perubahan bentuk dan struktur sajian musik gamat di masyarakat. Untuk membahasnyadigunakan teori dekonstruksi dan estetika dengan metode kualitatif. Dekonstruksi estetika musikgamat merupakan bentuk baru dari unsur tradisi dan modern, terdiri atas struktur yang saling terkaitdan membentuk sebuah sistem. Berdasarkan bentuknya, struktur ketradisian musik gamat mengalamipercampuran pada idiom instrumen, tangga nada, struktur permainan dan peran musisi, strukturlagu-lagu, serta konteks dan waktu pertunjukan. Berdasarkan penelitian disimpulkan bahwa estetikakeberagaman terwujud dari rasa saling menerima antarbudaya yang berbeda dalam pertunjukanmusik gamat. Dekonstruksi estetika musik gamat mengandung makna makna pembauran, kreativitasdan ekspresi serta estetika multikultural.Deconstruction of Aesthetics and Meaning of Gamat Music in Sawahlunto, West Sumatra.The variety of local social culture can be seen in the richness of cultural artistic expression, among others is inGamat music. This study deconstructs the aesthetics and meaning of the phenomena of the changes in formand structure toward the presentation of Gamat music in that society. For this purpose the deconstructionaland aesthetic theory are used with qualitative method. The deconstruction of the aesthetics of Gamat musicrepresents a new form from the traditional and modern element. It consists of interrelated structure andforms a system. Seen from its form, the structure of the tradition of Gamat music undergoes the mixture ofinstrumental idiom, the scale, the structure of performance and the role of musicians, the structure of thepieces as well as the context and time of performance. From the research results, it may be concluded thatthe aesthetics of diversity is formed from the sense of mutual acceptance towards different cultures in theperformance of Gamat music. The deconstruction of the aesthetics of Gamat music embodies the meanings of social integration, creativity and expresssion, and multicultural aesthetics as well.